Ekspansi Pasar Ekspor Indonesia: Meningkatkan Daya Saing di Kawasan Asia dan Global - alfiyanti, novita achadya (Maliki Interdisciplinary Journal, 2025)
Expansion of Indonesia's export market is the main strategy to encourage national economic growth and increase competitiveness at the Asian and global levels. This article outlines various steps that can be taken to increase the competitiveness of Indonesian exports, including product diversification, improving quality that meets international standards, implementing industry 4.0 technology, improving human resource skills are also considered important. export value is still high, Indonesia is still very dependent on exports of raw materials and commodities, making it vulnerable to price fluctuations in the global market. Dependence on raw materials also means that the added value generated by exports is relatively low compared to countries that focus more on high value-added products, such as the technology and innovation industries.With these strategies, Indonesia can strengthen its position in the global market and face international competition better.